CHEMICALLY CROSS-LINKED HYDROGEL HAVING HIGH MECHANICAL STRENGTH - Kabir, M. Hasnat; Amano, Yoshitaka; Harada, Sho; Gong, Jin; Furukawa, Hidemitsu (European Scientific Journal, ESJ, 2015)
The mechanically tough shape memory gel (SMG) was synthesized. The chemically cross-linked process was applied using a cross-linker named methylenebisacrylamide (MBAA). The SMG was prepared by N, Ndimethyl acrylamide (DMAAm) and stearyl acrylate (SA). The DMAAm is a hydrophilic monomer, whereas SA is a hydrophobic monomer. Due to the transparency, shape memory property, low friction, and high water content, the SMG is suitable for biomedical and optical applications. The physical property such as mechanical strength of most hydrogels is not good enough. However, the properties of these hydrogels are easily controlled by changing the polymer concentration, molecular weight and cross-linker concentrations. It is found that the swelling degree increases with respect to the DMAAm concentration. The mechanical properties of transparent shape memory hydrogel were investigated by the tensile, the compression and the dynamic mechanical analysis. The Young’s modulus gradually decreases with the increase of hydrophilic components. On the other hand, higher Young’s modulus is observed by increasing the high hydrophobic concentration. It is also seen that the mechanical stress decreases with respect to the temperature, indicating the loss of Young’s modulus. The result of dynamic mechanical analysis designates that the water swollen sample has both the elastic and viscous properties.